Climate policy under technology spillovers - Rolf Golombek; Michael Hoel (University of Oslo, Department of Economics, 2003)
We study climate policy when there are technological spillovers between countries, and there is no instrument that (directly) corrects for these externalities. Without an international climate agreement, the (non-cooperative) equilibrium depends on whether countries use tradable quotas or carbon taxes as their environmental policy instruments. All countries are better off in the tax case than in the quota case. Two types of international climate agreements are then studied: One is a Kyoto type of agreement where each country is assigned a specific number of internationally tradable quotas. In the second type of agreement a common carbon tax is used domestically in all countries. None of the cases satisfy the conditions for the social optimum. Even if the quota price is equal to the Pigovian level, R&D investments will be lower than what is socially optimal in the Kyoto case. It is also argued that the quota agreement gives higher R&D expenditures and more abatement than the tax agreement.
Keywords: H23; O30; Q20; Q28; Q48; 330; Climate policy; international environmental agreements; R&D; technology spillovers; Klimaschutz; Umweltabkommen; Forschung; Spillover-Effekt; Emissionsrechte; Ökosteuer; Theorie